Qualidade de sementes de porongo: condicionamento fisiológico associado a inseticidas e teste de frio - Zini, Priscila Barbieri (2018)
The cultivation of the porongueiro (Lagenaria siceraria (Mol.) Standl) in Rio Grande do Sul is linked to the gaucho habit of drinking chimarrão. However, despite the economic importance and due to the regional cultivation, agronomic studies that aim to give technical support to the producer are scarce. For, phytosanitary problems, such as attack of several pests, especially of Diabrotica speciosa, are the main cause of damages to the crop, from the plantar phase to the fruiting. Another, problematic is the exchange of seeds between the producers without control in the quality of the same ones, resulting in uneven percentages of germination, with failures in the stabilization of the stand of plants in the field. Thus, the present work had as objective to evaluate the physiological quality of the porongo seeds submitted to physiological conditioning methods associated to chemical treatments and to propose a methodology for the cold test in the seed vigor analysis. In order to achieve the objectives, two different experiments were carried out. The first objective was to evaluate the physiological quality of porongo seeds submitted to physiological conditioning methods associated with insecticides. The seeds were submitted to two forms of conditioning: hydrocondicionamento with prehydration in distilled water for 32 h; and pre-hydration in PEG 6000 solution for 48 h and seeds without conditioning. After conditioning, the insecticides of active ingredients were applied: imidacloprid, fipronil and thiamethoxam, at doses of 100, 200 and 300 ml for 100 kg-1 of seeds. Germination, first germination count, seedling length and mass, germination speed index, mean germination time, field emergence, emergency speed index, mean emergency time and relative germination frequency were evaluated. It was verified that the hydrocondicionamento and the osmocondicionamento were not effective to improve the expression of the first count of germination and germination of the porongo seeds, however, they were efficient for the rate of germination and emergence, and the average time of emergence of these seeds. The insecticides imidacloprid, fipronil and thiamethoxam have been beneficial for the phytosanitary treatment of porongo seeds, since they do not alter the physiological quality of the seeds. In the second experiment the objective was to improve the methodology of the cold test for porongo seeds, testing different substrates in combinations of low temperatures and periods of exposure to cold. The cold test was performed on paper roll and plastic boxes with soil and commercial substrate, in two cold temperatures (10 and 15 ° C), for periods of exposure of three, five and seven cold days. The methodology of the cold test using the roll of paper was shown as a more viable option, in which the differentiation in three levels of vigor without loss of the physiological potential of the lots can be obtained with period of exposure of seven days to the cold of 10 or 15 ° C. The tests of first germination, germination and root dry mass counts showed significant correlations with the different cold test methodologies. With this study it can be verified that the different conditioning methods used were efficient to improve only some of the variables used in the evaluation of the physiological quality of the seeds, and that, the cold functioned as a conditioning agent for the porongo seeds.